Perfil de aptidão cardiorrespiratória em corredores jovens pela cinética do VO2 em testes progressivos e retangulares - Massini, Danilo Alexandre [UNESP] (2015)
This study compared the kinetics of VO2 during transitions in the Respiratory Compensation Point (RPC) and Critical Speed (CS), as well as analyze the changes in aerobic fitness after a training period. The participants (n = 10; age: 15.8 ± 1.7 years; height: 1.7 ± 0.1 meters; body mass: 57.1 ± 12.4 kg) were undergone to the progressive test (initial velocity at 7.0 km×h-1 and increments of 1.0 km×h-1 every minute until voluntary exhaustion). The VO2 was measured breath-by-breath, and the maximum value (V̇ O2max) was considered the higher 9s averaged V̇ O2. The Gas Exchange Threshold (GET) and RCP were determined following respiratory criterion (VE/VO2, PETO2, VE/VCO2 and PETCO2). The iV̇ O2max was considered the smallest speed leading to V̇ O2max. The CS was determined by constant load tests performed in random order at the intensities of 85, 90 and 110% iV̇ O2max, performed until voluntary exhaustion, with 24 hours apart. The values of speed and time to exhaustion (tLim) were adjusted by linear model (S = W' × (1/t) + CS), where W' is the finite energy store. The VO2 kinetics was analyzed by a mono-exponential function with time-delay (TD), giving time constant (τ) and the primary amplitude response (A1'). The slow component (SC) was determined by subtracting A1' from the final V̇ O2 response (EEV̇ O2). For the analysis of V̇ O2 profile during progressive test was applied the slope of linear adjustment between VO2 vs. time for each zone of exercise intensity: Z1 = Speed ≤ GET; Z2 = GET < Speed ≤ RCP; and Z3 = Speed > RCP. The coefficient of variance (R2) examined the correlation between the values of VO2 RCP and CS. The ANOVA (one-way) test, using Bonferroni as post-hoc, compared the differences between the indexes of aerobic capacity (GET, RCP and CS) and the slope coefficients of V̇ O2 profile during progressive test before and after training. Significance level was set at p ≤ ...